Blood glucose, plasma insulin and sensory responses to guar-containing wheat breads: effects of molecular weight and particle size of guar gum - Ellis, Peter R.; Dawoud, Fathy M.; Morris, Edwin R. (British journal of nutrition, 1991)
The effectiveness of guar gum in reducing post-prandial blood glucose and plasma insulin levels in human subjects seems to depend mainly on its ability to increase the viscosity of digesta in the small intestine. However, the precise relationship between the rheological properties of guar gum (either in vitro or in vivo) and the changes in blood metabolites and hormones is unknown. The aim of the present study, therefore, was to investigate the effects of wheat breads containing guar gum samples varying in molecular weight (Mw) and particle size (characteristics that strongly influence the rheological properties of guar gum) on post-prandial blood glucose and plasma insulin levels in healthy subjects. The sensory qualities of breads containing guar-gum flours of different Mw were also evaluated using a hedonic scoring technique. No significant differences in the post-prandial blood glucose responses were found between the control and guar breads. However, all the guar breads elicited significant (P < 0.05) decreases in the post-prandial rise in plasma insulin, an effect that did not appear to be influenced by large variations in Mw or particle size of guar gum. Moreover, the sensory qualities of guar bread were markedly improved by using low Mw grades of guar gum.